Multicenter study of endoscopic preoperative biliary drainage for malignant distal biliary obstruction - Sasahira, Naoki (World J Gastroenterol, 2016)
AIM: To determine the optimal method of endoscopic preoperative biliary drainage for malignant distal biliary obstruction. METHODS: Multicenter retrospective study was conducted in patients who underwent plastic stent (PS) or nasobiliary catheter (NBC) placement for resectable malignant distal biliary obstruction followed by surgery between January 2010 and March 2012. Procedure-related adverse events, stent/catheter dysfunction (occlusion or migration of PS/NBC, development of cholangitis, or other conditions that required repeat endoscopic biliary intervention), and jaundice resolution (bilirubin level < 3.0 mg/dL) were evaluated. Cumulative incidence of jaundice resolution and dysfunction of PS/NBC were estimated using competing risk analysis. Patient characteristics and preoperative biliary drainage were also evaluated for association with the time to jaundice resolution and PS/NBC dysfunction using competing risk regression analysis. RESULTS: In total, 419 patients were included in the study (PS, 253 and NBC, 166). Primary cancers included pancreatic cancer in 194 patients (46%), bile duct cancer in 172 (41%), gallbladder cancer in three (1%), and ampullary cancer in 50 (12%). The median serum total bilirubin was 7.8 mg/dL and 324 patients (77%) had ≥ 3.0 mg/dL. During the median time to surgery of 29 d [interquartile range (IQR), 30-39 d]. PS/NBC dysfunction rate was 35% for PS and 18% for NBC [Subdistribution hazard ratio (SHR) = 4.76; 95%CI: 2.44-10.0, P < 0.001]; the pig-tailed tip was a risk factor for PS dysfunction. Jaundice resolution was achieved in 85% of patients and did not depend on the drainage method (PS or NBC). CONCLUSION: PS has insufficient patency for preoperative biliary drainage. Given the drawbacks of external drainage via NBC, an alternative method of internal drainage should be explored.